De-securitizing the "Silk Road": Uzbekistan's cooperation agenda with Russia, China, Japan, and South Korea in the post-Karimov era. Issue 2 (July 2020) - Dadabaev, Timur
This article argues that Uzbekistan's cooperation agenda with Russia, China, Japan, and South Korea demonstrates clear signs of breaking with the Karimov-era security-driven agenda for cooperation in favor of de-securitization. This article uses a comparative analysis of the engagement of Russia, China, Japan, and South Korea with Uzbekistan through an analysis of the shifting political discourses in Uzbekistan and these states, statistics regarding their interaction, and an analysis of the economic road maps of their engagement from 2015 onward. This timeframe is attributed particular importance in this article, as it symbolizes the new opening of Uzbekistan toward these four states after the death of its dictatorial President Islam Karimov. In terms of the narrative, this article will first explore the problem of the securitization of the Central Asian region and the cooperation agenda. The article then discusses the motivations of Uzbekistan and its cooperation counterparts in pursuing closer ties. This discussion will then be followed by an analysis of how the new leadership in Uzbekistan re-evaluated its past behavior to address its post- and neocolonial challenges and the cooperation agendas with Russia, China, South Korea, and Japan.